Synthesis, Characterization of New Metal Complexes of Co (II), Cu (II), Cd (II) and Ru (III) from azo ligand 5-((2-(1H-indol-2-yl)ethyl) diazinyl)-2- aminophenol, Thermal and Antioxidant Studies (Baghdad Science Journal, 2023)
A novel metal complexes Cu (II), Co (II), Cd (II), Ru (III) from azo ligand 5-((2-(1H-indol-2-yl) ethyl) diazinyl)-2-aminophenol were synthesized by simple substitution of tryptamine with 2-aminophenol. Structures of all the newly synthesized compounds were characterized by FT IR, UV-Vis, Mass spectroscopyand elemental analysis. In addition measurements of magnetic moments, molar conductance and atomic absorption. Then study their thermal stability by using TGA and DSC curves. The DCS curve was used to calculate the thermodynamic parameters ΔH, ΔS and Δ G. Analytical information showed that all complexes achieve a metal:ligand ratio of [1:1]. In all complex examinations, the Ligand performs as a tridentate ligand, connecting Cu (II), Co (II), Cd (II), and Ru (III) ions through the nitrogen atom of amine , azo groups and the oxygen phenolic group. Cu (II), Co (II), and Cd (II) complexes were characterized as having tetrahedral geometry, while Ru (III) complex was found to have octahedral geometry. The antioxidant activity of the metal complexes was assessed against the DPPH radical (1.1-diphenyl-2-picrylhydrazyl) and compared to that of a common natural antioxidant Gallic acid to observe the produced compounds. The results demonstrated ligands have more antioxidant activity than metal complexes.